2017
DOI: 10.1017/jfm.2017.844
|View full text |Cite
|
Sign up to set email alerts
|

Gel-controlled droplet spreading

Abstract: Spreading and stationary droplets of a thermally responsive fluid on a heated surface are studied. The fluid undergoes a reversible gel formation at elevated temperature. The spatio-temporal pattern of gel formation within the droplet is examined using an experimental method based on spectral domain optical coherence tomography and time varying speckle patterns. Two stages of gel formation can be distinguished: first, a thin crust appears starting at the contact line. Second, a gel layer appears above the heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…For both mechanisms discussed above the solidification is assumed to be initiated at the contact line. This is recently confirmed explicitly for slowly spreading Pluronic F127 [9]. In these experiments the temporal evolution of the gelation front inside the drop was resolved, displaying several interesting features such as the formation of a thin crust over the free surface.…”
Section: A Mechanism Of Solidification-induced Pinningsupporting
confidence: 66%
See 2 more Smart Citations
“…For both mechanisms discussed above the solidification is assumed to be initiated at the contact line. This is recently confirmed explicitly for slowly spreading Pluronic F127 [9]. In these experiments the temporal evolution of the gelation front inside the drop was resolved, displaying several interesting features such as the formation of a thin crust over the free surface.…”
Section: A Mechanism Of Solidification-induced Pinningsupporting
confidence: 66%
“…The rate of evaporation even diverges for contact angles below 90 • [21][22][23][24]. The role of solvent evaporation for gel formation in Pluronic was also invoked in [9]. For all these reasons we experimentally verified the possible influence of %RH on the spreading dynamics and final radius.…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…A few studies have previously investigated the impact and spreading of viscoplastic droplets on a solid surface. It is shown that yield stress can prohibit the recoil of the droplet, retard the deformation after the drop has reached the maximum shape, and prevent splashing (German & Bertola 2009;Luu & Forterre 2009;Jalaal & Stoeber 2014;Blackwell et al 2015;Jalaal, Balmforth & Stoeber 2015;Jalaal 2016;Jalaal et al 2018).…”
mentioning
confidence: 99%
“…OCT imaging techniques have also been increasingly developed and applied across a broad a range of different disciplines, for example, the non-invasive analysis of paintings for art history and conservation [24], and profiling surface membranes for reconfigurable optics applications [25]. OCT developments and applications which involve imaging liquids and liquid surfaces have included micro-rheology studies of simple and complex fluids [26], analysing capillary waves in biological fluids [27,28], droplet imaging [29] and interface imaging to study surface wettability [30], gelation [31], and evaporation [32].…”
Section: Introductionmentioning
confidence: 99%